Identification of miR-342-5p/MDM4/p53 network in acute myeloid leukemia - Misir, Sema; Ozer Yaman, Serap; Hepokur, Ceylan; Akidan, Osman; Aliyazicioglu, Yuksel; Enguita, Francisco J.; Al Zoubi, Mazhar Salim (Frontiers in Cell Death, 2024)
Acute myeloid leukemia (AML) is one of the most prevalent hematological malignancies. miRNAs are involved in cancer initiation and progression in various cancer types by post-transcriptional regulation of gene expression. The aim of this study is to investigate the mechanisms in the development and progression of acute myeloid leukemia and to identify potential target genes and miRNAs by bioinformatic analysis. miRNA expression profiles were obtained from the GSE51908 dataset on the Gene Expression Omnibus (GEO). GEO2R was used to identify differentially expressed miRNAs. The diagnostic and overall survival effects of the identified miRNA were determined using ROC analysis and Kaplan-Meier curve, respectively. Putative miRNA targets were determined based on miRWalk and miRDB tools. The expression change and overall survival analysis of the identified target gene were analyzed by Gene Expression Profiling Interactive Analysis (GEPIA). Protein-protein interaction (PPI) networks of the target gene were determined using STRING and GeneMANIA. Functional enrichment analysis was performed using the DAVID program. 24 DE-miRNAs were identified, including 16 upregulated and 8 downregulated genes. miR-342-5p expression had significantly shorter survival than those in higher expression control group (p = 0.0001), and its AUC value to discriminate AML from control groups was 0.795. High expression of MDM4 predicts an unfavorable prognosis in AML patients. The MDM4 gene was determined to be associated with decreased survival rates. According to KEGG results, microRNAs, p53 signaling pathway, and cell cycle are associated with AML development. The current study based on the GEO database, miR-342-5p/MDM4/p53 axis AML may provide new therapeutic targets.